2007
DOI: 10.1093/brain/awm271
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and morphological phenotype of the filamin myopathy: a study of 31 German patients

Abstract: Mutations in the filamin C gene (FLNC) cause a myofibrillar myopathy (MFM), morphologically characterized by focal myofibrillar destruction and abnormal accumulation of several proteins within skeletal muscle fibres. We studied 31 patients from four German families to evaluate the phenotype of filaminopathy. All patients harboured the same p.W2710X mutation in FLNC. Haplotype analysis suggested a founder mutation in these German filaminopathy families. The mean age at onset of clinical symptoms was 44 +/- 6 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
150
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(166 citation statements)
references
References 42 publications
12
150
1
3
Order By: Relevance
“…2 The family history of respiratory compromise developing a decade after the onset of weakness as seen in our patient is typical of FLNC-MFM. Being of German descent also favors the diagnosis of FLNC-MFM, given that the founder FLNC mutation has been reported in German patients.…”
Section: Discussionsupporting
confidence: 54%
“…2 The family history of respiratory compromise developing a decade after the onset of weakness as seen in our patient is typical of FLNC-MFM. Being of German descent also favors the diagnosis of FLNC-MFM, given that the founder FLNC mutation has been reported in German patients.…”
Section: Discussionsupporting
confidence: 54%
“…In this regard, the finding that expression of these mutants in cardiac myocytes resulted in the formation of larger protein aggregates than when expressed in C2C12 myotubes supports a model in which interaction of these mutants with tissue-specific proteins, contributes to the predominant cardiac phenotype. In this regard, it is also remarkable that about one-third of myofibrillar myopathy patients with the most frequent mutation in FLNC (the German variant, p.W2710X) are reported to have cardiac abnormalities, although only two out of 25 patients had cardiomyopathy with left ventricular dysfunction 13 . These data suggest that the clinical spectrum of the different filaminopathies is highly dependent on the site of mutation within the filamin C molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mutations in FLNC have been previously associated with myofibrillar myopathy (MIM 609524) 12,13 . However, none of the patients diagnosed with HCM in our study showed symptoms of myofibrillar myopathy, including nine subjects older than 44 years, which is the mean age at onset reported for the most common mutation in FLNC (p.W2710X) 13 . Four HCM patients with mutations in FLNC were studied by electromyography and magnetic resonance imaging with negative results.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Rudolf A. Kley and Matthias Vorgerd discussing ''The phenotype of myofibrillar myopathy associated with p.W2710X mutation in filamin C in 31 German patients" had examined 31 patients from four German families to evaluate the phenotype of filaminopathy [35], a novel form of myofibrillar myopathy (MFM) [36]. All patients harboured the same p.W2710X mutation in the dimerization domain of the filamin C gene on chromosome 7q32.1.…”
Section: Filaminmentioning
confidence: 99%